Microneedle Assisted Micro‐Particle Delivery from Gene Guns: Experiments Using Skin‐Mimicking Agarose Gel. Issue 2 (7th January 2014) - Zhang, Dongwei; Das, Diganta B.; Rielly, Chris D.
<x xml:space="preserve">Abstract</x> A set of laboratory experiments has been carried out to determine if micro‐needles (MNs) can enhance penetration depths of high‐speed micro‐particles delivered by a type of gene gun. The micro‐particles were fired into a model target material, agarose gel, which was prepared to mimic the viscoelastic properties of porcine skin. The agarose gel was chosen as a model target as it can be prepared as a homogeneous and transparent medium with controllable and reproducible properties allowing accurate determination of penetration depths. Insertions of various MNs into gels have been analysed to show that the length of the holes increases with an increase in the agarose concentration. The penetration depths of micro‐particle were analysed in relation to a number of variables, namely the operating pressure, the particle size, the size of a mesh used for particle separation and the MN dimensions. The results suggest that the penetration depths increase with an increase of the mesh pore size, because of the passage of large agglomerates. As these particles seem to damage the target surface, then smaller mesh sizes are recommended; here, a mesh with a pore size of 178 μm was used for the majority of the experiments. The operating pressure provides a positive effect on the penetration depth, that is it increases as pressure is increased. Further, as expected, an application of MNs maximises the micro‐particle penetration depth. The maximum penetration depth is found to increase as the lengths of the MNs increase, for example it is found to be 1272 ± 42, 1009 ± 49 and 656 ± 85 μm at 4.5 bar pressure for spherical micro‐particles of 18 ± 7 μm diameter when we used MNs of 1500, 1200 and 750 μm length, respectively. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:613–627, 2014